Beyond altruistic philosophy: a study on the determinants of organic food consumer involvement - Barros, José Eduardo de Melo; Cabral, Romilson Marques; de Oliveira, Brigitte Renata Bezerra; Melo, Francisco Vicente Sales; Bastos, Tarcísio Regis de Souza (Contextus - Revista Contemporânea de Economia e Gestão, 2018)
The awareness of ecological preservation and the search for healthy food were widespread ideas in the 1970s. In the late 1980s, new parameters were added to that ideological motivation. This article aimed to understand the involvement of organic product consumers. The literature review developed in this work approaches the involvement construct, its multidimensionality and its measurement, as well as the determinants of high involvement with organic food. The data were collected through an online survey, whose sample consisted of 412 valid respondents. Descriptive and inferential statistics techniques, mainly factorial analysis and logistic regression, were used. In general, it is possible to affirm that the hypotheses were partially confirmed. It is concluded that involvement with organic products occurs in a multifaceted way and the determinants that distinguish highly involved individuals may be associated with selfish circumstances and specific buying situations, such as greater regularity and willingness to pay higher prices.